Malta : 2012 Article IV Consultation: Staff Report; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2012)
This Article IV Consultation reports that Malta's economy continues to perform well amidst considerable turbulence in the euro area. While spillovers have remained contained to date, Malta's large financial sector and highly open economy heighten contagion and financial stability risks. The government, which has a one-seat majority in Parliament, narrowly survived a vote of no confidence. The policy challenge is to maintain growth and employment while building buffers against a highly uncertain international environment.